The marketing performance blueprint : strategies and technologies to build and measure business success - Roetzer, Paul, 1978- (John Wiley & Sons, 2014)
Discover what's possible when the art and science of marketing collide The Marketing Performance Blueprint is an actionable and innovative guide to unlocking your potential as a marketer and accelerating success for your business. With an eye toward the marketing industry's rapid evolution, this book focuses on the processes, technologies, and strategies that are redefining the marketing environment. Step by step, you will learn how to build performance-driven organizations that exceed ROI expectations and outpace the competition. Companies are demanding a more technical, scientific approach t.